One-year evaluation of a new restorative glass ionomer cement for the restoration of non-carious cervical lesions in patients with systemic diseases: a randomized, clinical trial (Journal of Applied Oral Science, 2021)
Objective: This randomized and clinical trial aimed to evaluate the performance of a new restorative Glass Ionomer Cement (GIC) for the restoration of non-carious cervical lesions (NCCLs) of patients with systemic diseases compared with a posterior resin composite after 12 months. Methodology: 134 restorations were placed at 30 patients presenting systemic diseases by a single clinician. NCCLs were allocated to two groups according to restorative system used: a conventional restorative GIC [Fuji Bulk (GC, Tokyo Japan) (FB)] and a posterior resin composite [G-ænial Posterior (GC, Tokyo Japan) (GP)] used with a universal adhesive using etch&rinse mode. All restorative procedures were conducted according to manufacturer’s instructions. Restorations were scored regarding retention, marginal discoloration, marginal adaptation, secondary caries, surface texture, and post-operative sensitivity using modified United States Public Health Service (USPHS) criteria after 1 week (baseline), 6, and 12 months. Descriptive statistics were performed using chi-square tests. Cochran Q and Mc Nemar’s tests were used to detect differences over time. Results: After 12 months, recall rate was 93% and the rates of cumulative retention failure for FB and GP were 4.9% and 1.6% respectively. Both groups presented similar alpha rates for marginal adaptation (FB 86.2%, GP 95.5%) and marginal discoloration (FB 93.8%, GP 97%) at 6-month recall, but FB restorations showed higher bravo scores than GP restorations for marginal adaptation and marginal discoloration after 12 months (p<0.05). Regarding surface texture, 2 FB restorations (3.1%) were scored as bravo after 6 months. All restorations were scored as alpha for secondary caries and postoperative sensitivity after 12 months. Conclusion: Although the posterior resin composite demonstrated clinically higher alpha scores than the conventional GIC for marginal adaptation and discoloration, both materials successfully restored NCCLs at patients with systematic disease after a year. Clinical relevance: Due to its acceptable clinical results, the tested conventional restorative GIC can be used for the restoration of NCCLs of patients with systemic diseases.